Atlas of Hematopathology with 100 Case Studies - Naeim Md, Faramarz; Naeim Md, Faramarz; Rao, P. Nagesh; Song, Sophie X. (Academic Press, 2024)
Atlas of Hematopathology with 100 Case Studies is a practical guide useful for pathologists and hematologists, residents and fellows, laboratory directors, researchers, and students in the field of hematology, cytogenetic, and molecular pathology. The book offers important information to practicing physicians and those in pathology and hematology training to improve their diagnostic skills. It covers the most important aspects of hematopathology, including classifications, clinical symptoms, hematopathologic features, diagnostic criteria, differential diagnosis, and the use and importance of ancillary testing, such as immunohistochemistry, flow cytometry, and cytogenetics. - Includes case studies that provide a brief clinical history, along with images with relevant questions and answers - Provides user-friendly tables and graphs, along with correlations between microscopic findings and images of ancillary test results - Features over 250 color photographs that demonstrate various pathologic aspects of the disease